Análise de uma sessão de treino de força com repetição parcial e total em atletas do powerlifting paralímpico - Mendonça, Tanise Pires (2019)
Introduction: Paralympic Powerlifting is a sport that is not an exercise force. The training aims at gaining strength, which uses a range of motion as one of the variables for the development of maximum strength. Objective: To evaluate the effect of a training session with partial (130% 1RM) and total (90% 1RM – use of Boards) on fatigue index (IF), peak torque (PT), time to peak torque, strength development rate (TDF), muscle thickness (USG) and muscles activation (EMG) in Paralympic Powerlifting (PP) athletes. Twelve athletes of national level of the PP participated, during three weeks (with 28.60 ± 7.60 years, 71,80 ± 17,90 kg) and with experience of minimum training of 12 months. An ANOVA (Two Way) was performed for repeated measures, and Bonferroni Post Hoc, with p <0.05. Results: There were no significant differences in the strength indicators (IF: 76.12 and 61.02, TDF: 640.43 and 602.78, Time: 0.72 and 0.64 and PT: 1119.68 and 771, 63N) under conditions with partial and total replications respectively. Regarding the muscular activation measured through the EMG, there were no significant differences between the muscles evaluated during the exercises. As for edema in the Clavicular portion of the Greater Pectoral Muscle (3.03 and 3.34 cm, p = 0.001) and Esternal Portion (2.97 and 3.33 cm, p = 0.001) there were significant differences between the interventions with partial repetitions and totals respectively. Conclusion: It was verified that the training with partial repetitions and with complete repetitions did not present significant differences in the variables of strength and muscular activation, although the training with partial repetitions was performed with greater absolute loads. Training with complete repetitions had a larger edema, which tends to provide increased fatigue during training.